A Scoping Review to Assess Sexual and Reproductive Health Outcomes, Challenges and Recommendations in the Context of Climate Migration - van Daalen, Kim Robin; Dada, Sara; Issa, Rita; Chowdhury, Maisoon; Jung, Laura; Singh, Lucy; Stokes, Diarmuid; Orcutt, Miriam; Singh, Neha S. (Frontiers in Global Women's Health, 2021)
As growing numbers of people are forced to migrate due to climate change and variability, it is important to consider the disparate impacts on health for vulnerable populations, including sexual and reproductive health (SRH). This scoping review aims to explore the relationship between climate migration and SRH. We searched PubMed/MEDLINE, CINAHL Plus, EMBASE, Web of Science, Scopus, Global Health and Google for peer-reviewed and grey literature published before 2nd July 2021 that reported on SRH in the context of climate migration. Data were extracted using a piloted extraction tool and findings are reported in a narrative synthesis. We screened 1607 documents and included ten full-text publications for analysis: five peer-reviewed articles and five grey literature documents. Reported SRH outcomes focused on maternal health, access to family planning and antiretroviral therapy, sexual and gender-based violence, transactional sex, and early/forced marriage. Recommendations to improve SRH in the climate migration context called for gender-transformative health systems, behaviour change communication, and the involvement of local women in policymaking and programme implementation. The SRH outcomes reported in the literature focus on a relatively narrow range of SRH domains, emphasizing women and girls, over men. Achieving holistic and equitable SRH in the context of climate migration requires engaging all genders across the range of SRH outcomes and migration contexts. This review highlights the need for further empirical evidence on the effect of climate migration on SRH, with research that is context-specific and engages communities in order to reflect the heterogeneity of impact in the climate-migration-SRH nexus.